Effect of Backbone Variation on Properties of Fluorinated Polyimides toward Optoelectronic Applications. Issue 15 (6th June 2016) - Grabiec, Eugenia; Kotowicz, Sonia; Siwy, Mariola; Grucela, Marzena; Schab‐Balcerzak, Ewa
Abstract : The fluorinated polyimides are synthesized from 4, 4′‐(hexafluoroisopropylidene)diphthalic anhydride and various diamines containing fluorene, anthraquinone, phenanthridine, stilbene, and fluorenylidene units. The polymers exhibit high glass transition temperature ( T g = 170–261 °C) and high thermal stability with decomposition temperatures ( T d ) in the range of 320–560 °C and 290–520 °C in nitrogen atmosphere and in air, respectively. The optical properties, that is, absorption in UV–vis range and photoluminescence of obtained polyimides, are investigated in solution and in solid state as a blend with inert poly(methyl methacrylate). The polymers in solution and in solid state emit light in the range of 356–572 nm depending on the polymer structure. Additionally, the photoluminescence properties of the polyimide containing phenanthridine units in the backbone before and after protonation with HCl and methanesulfonic acid are tested in N ‐methyl‐2‐pyrrolidone solution. All polyimides are electrochemically active and undergo an electrochemical reduction process as is found in cyclic voltammetry. The lowest unoccupied molecular orbital (LUMO) levels are found in the range from −3.58 to −3.93 eV. Abstract : The fluorinated polyimides show photoluminescence properties both in solution and in solid state. They emitt light with the maximum band located in voilet, blue, green, and yellow regions. Polymer with phenylphenanthridine moieties is the most perspective because it is soluble, shows adequate thermal properties, and there is a possibilty to improve the luminescence intensity of this polymer by doping.